PENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN PROPOSAL PENELITIAN TINDAKAN KELAS MELALUI MODEL PEMBINAAN CLCK (CONTOH, LATIHAN, CONTROL, KERJA MANDIRI) BERBASIS PENDAMPINGAN INTENSIF DI SDN 17 SIMAUNG CUMATEH - Eva Nelda (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTBased on observations on the competence of teachers at SDN 17 Simaung Cumateh in compiling a Class Action Research Proposal in the phenomenon found that the ability of teachers in compiling classroom action research is still low. The purpose of this study was to describe and obtain information about improving the ability of teachers in compiling Classroom Action Research Proposals through the CLCK coaching model (Example, Exercise, Control, Independent Work) Based on Intensive Assistance at Simaung Cumateh Elementary School. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 5 SDN 17 Simaung Cumateh teachers. Research data was collected using an observation sheet. Data is analyzed using percentages. Based on the results of the research and discussion, it can be concluded that the Intensive Assistance-Based CLCK coaching model can improve the ability of teachers in preparing Classroom Action Research Proposals at Simaung Cumateh Elementary School. Analysis of the quality of PTK proposals made by the teacher shows that the teacher's ability to compile a Class Action Research Proposal increases from cycle I to cycle II. The ability of the teacher in preparing the Class Action Research Proposal in cycle I was 71.50 (enough) to increase to 93.00 (good) in cycle II.Keywords: Teacher's Ability, Preparation of PTK Proposal, CLCK coaching model based on Intensive Assistance